ECONOMIC TRANSFORMATION OF THE INDONESIA–MALAYSIA BORDER REGION: FROM TRADITIONAL BARTER SYSTEMS TO A MODERN CROSS-BORDER TRADE ECOSYSTEM - Dina Octaviani; Rustam; Setyo Gunawan (Adisam Publisher, 2026)
This study examines the economic transformation of the Indonesia–Malaysia border region from traditional barter systems to a modern cross-border trade ecosystem. The research adopts a qualitative approach, drawing on recent Scopus-indexed literature, policy reports, and relevant academic sources. The findings reveal that the transformation process is multidimensional, involving the interactions among economic integration, institutional development, technological advancement, and socio-cultural adaptation. While the introduction of formal trade systems has enhanced market efficiency, expanded trade volumes, and improved regional connectivity, traditional barter practices and informal trade continue to persist, forming a hybrid economic structure in border areas. Furthermore, the study identifies key challenges, including institutional fragmentation, regulatory inconsistencies, limited infrastructure, and unequal access to economic opportunities, which contribute to uneven development across border regions. Digitalization is a critical driver of the transition toward a modern trade ecosystem, particularly through the expansion of e-commerce and digital financial services. However, socio-cultural factors remain influential, as local communities maintain traditional practices based on trust and social networks. This study contributes to the literature by providing an integrative perspective that bridges economic, institutional, and socio-cultural dimensions of border economic transformation. The findings highlight the importance of inclusive policy design that accommodates both formal and informal systems to ensure sustainable and equitable development.